AKTIVITAS PEMBELAJARAN SEBAGAI SUATU SISTEM - A. Qomarudin (STAI Ma'had Aly Al-Hikam Malang, 2021)
Education is an effort to develop the potential of students in the learning environment. So that in achieving these educational goals, it will not be separated from a good learning system. So it is necessary to understand that: learning activities are a unified whole (system) to achieve an expected goal; there are components of the learning system which broadly consist of input, process, output-outcome, and specifically consist of objectives, materials, methods, media, evaluation; There are several factors that influence the learning system, namely the factors of educators, students, infrastructure, and learning environment.